2016
DOI: 10.1177/0040517515617419
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of antistatic fiber with segmented pie structure

Abstract: In this study, multi-component antistatic fibers with segmented pie structures were prepared by conjugate spinning of carbon black (CB)/polybutylene terephthalate (PBT) and polyethylene terephthalate (PET) polymers. The antistatic property of the CB/PBT/PET fibers can be attributed to two factors: thorough mixing of the CB powder in the polymer matrix, and the close contacts formed between the segmented pie fibers. The fibers were woven and knitted into fabrics whose washing durability and antistatic propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These results indicate the effectiveness of blending PBT with carbon black particles to increase the conductivity of PBT. The increased conductivity can be attributed to the π–π* electron transitions in the C=C bonds of carbon black [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate the effectiveness of blending PBT with carbon black particles to increase the conductivity of PBT. The increased conductivity can be attributed to the π–π* electron transitions in the C=C bonds of carbon black [10].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the electrical resistivities of the DTYs are higher than those of the original fibers, which is most likely due to the deformation of the DTYs during processing, thereby lowering the degree of rigid contact between adjacent fibers. Previous reports have demonstrated that the presence of broken filaments and surface concaves are significant problems in DTYs because these affect the inter-filament contacts and electrical conductivity of such yarns [10]. As a result, the filler and the configuration and deformation of the fibers affect the electrical resistivity of the resulting product.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Furthermore, the lack of polar hydrophilicity of polyester fabric can also lead to the electrostatic accumulation of polyester fibers. [4][5][6] The rubbing motion leads to fibers repelling each other and generating static charges on the fabric surface, 7 which will affect comfort and limit their applications in apparel and home furnishings. 8,9 Static charge accumulated on the surface without appropriate dissipation, in certain circumstances, 10 can cause unwanted side effects such as attraction of dust, electric shocks, and even pose a fire hazard or lead to explosions.…”
mentioning
confidence: 99%